How the Political Economy of Knowledge Production Shapes Education Policy: The Case of Teacher Evaluation in Federal Policy Discourse. (September 2021) - Reckhow, Sarah; Tompkins-Stange, Megan; Galey-Horn, Sarah
Using congressional testimony on teacher quality from 2003 to 2015 and analysis of 60 elite interviews, we show how the political economy of knowledge production influences idea uptake in education policy discourse. We develop and assess a conceptual framework showing the organizational and financial infrastructure that links research, ideas, and advocacy in politics. We find that congressional hearing witnesses representing groups that received philanthropic grants are more likely to support teacher evaluation policies, but specific mentions of research in testimony are not a factor. Overall, our study shows that funders and advocacy groups emphasized rapid uptake of ideas to reform teacher evaluation, which effectively influenced policymakers but limited the use of research in teacher evaluation policy discourse.